The Role of Self-Control as a Mediator of the Relationship Between Financial Knowledge and Impulsive Buying Behavior of Facebook Marketplace Users from an Islamic Perspective (A Study of Generation Z in Bandar Lampung City) - Daus HARTONO; Vicky F SANJAYA; Nurhayati NURHAYATI (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the role of self-control as a mediating variable in the relationship between financial knowledge and impulsive buying behavior among Generation Z Facebook Marketplace users in Bandar Lampung City from an Islamic perspective. This study used a quantitative method by distributing questionnaires to 100 respondents and data analysis was conducted using SmartPLS 4.0 to test the PLS-SEM model. The results showed that financial knowledge had a positive and significant effect on self-control, while self-control had a negative and significant effect on impulsive buying behavior. However, self-control was unable to significantly mediate the relationship between financial knowledge and impulsive buying behavior. This finding indicates that financial knowledge alone is not enough to suppress impulsive behavior without strong self-control. From an Islamic perspective, these results emphasize the importance of implementing the values ​​of israf (moderation) and tabdzīr (not wasteful) in shaping wise financial behavior. This study contributes to the development of Islamic financial behavior literature and provides insights for the younger generation to be more rational and ethical in shopping in the digital era. Future research is recommended to add variables such as lifestyle, social pressure, or religiosity to broaden understanding of the factors that influence consumer behavior.